Psychological Coping and Well-Being of Male Latino Undergraduates - Gloria, Alberta M. (2009)
This study examined 100 male Latino undergraduates' cultural self-esteem, perceived educational barriers, cultural fit, coping responses (CRs), and subsequent well-being within higher education. The most commonly reported CR for Latino males was to actively find out more about the situation and take a positive planned action. Assessing group mean differences, a class standing by generation interaction revealed that first-generation lower division and first-generation upper division students reported higher perceptions of barriers to staying in school than second-generation lower division and second-generation upper division students, respectively. Similarly, examining differences of coefficients, the strength of the relationship of perceptions of barriers to staying in school and psychological well-being was significantly stronger for the first-generation than second-generation male students Cultural congruity and emotion-focused coping were most predictive of psychological well-being; however, perception of barriers to staying in school was consistently evident in understanding male Latino undergraduates' educational experiences.